1993
DOI: 10.1152/jn.1993.70.6.2684
|View full text |Cite
|
Sign up to set email alerts
|

(RS)-alpha-methyl-4-carboxyphenylglycine neither prevents induction of LTP nor antagonizes metabotropic glutamate receptors in CA1 hippocampal neurons

Abstract: 1. The effects of the putative antagonist of metabotropic glutamate receptors (mGluR), (RS)-alpha-methyl-4-carboxyphenylglycine (MCPG), were investigated in CA1 hippocampal neurons using intracellular and extracellular recordings. 2. MCPG (0.5 mM) did not antagonize the characteristic block of the slow afterhyperpolarization and spike accomodation produced by the selective mGluR agonist, 1S,3R-1-aminocyclopentane-1,3-dicarboxylic acid (1S,3R-ACPD) (30 microM). 3. MCPG (0.5 mM) did not prevent the inward curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 0 publications
4
47
0
Order By: Relevance
“…The GABA B and adenosine A 1 receptor-induced presynaptic inhibition of EPSPs is of a rapid onset and fully reversible within 5-10 min after agonist application. 22,57 The depression of the fEPSPs produced by activation of the presynaptic metabotropic glutamate receptor, however, lasts more than 15 min after the termination of agonist application, 5,10,35 which is comparable to that elicited by LFS (see Fig. 2 for comparison).…”
Section: Discussionmentioning
confidence: 78%
“…The GABA B and adenosine A 1 receptor-induced presynaptic inhibition of EPSPs is of a rapid onset and fully reversible within 5-10 min after agonist application. 22,57 The depression of the fEPSPs produced by activation of the presynaptic metabotropic glutamate receptor, however, lasts more than 15 min after the termination of agonist application, 5,10,35 which is comparable to that elicited by LFS (see Fig. 2 for comparison).…”
Section: Discussionmentioning
confidence: 78%
“…This has previously been reported by some groups (Bashir et al, 1993;Bortolotto et al, 1995;Richter-Levin et al, 1994;Riedel et al, 1995), and not by others (Chinestra et al, 1993;Manzoni et al, 1994;Selig et al, 1995). Also work from mGluR5 knockout mice have shown that NMDA-receptor mediated LTP is impaired in these animals (Jia et al, 1998;Lu et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…The involvement of the mGluRs in hippocampal LTD has been well established (Bolshakov and Siegelbaum, 1994;Fitzjohn et al, 1999;O'Mara et al, 1995;Snyder et al, 2001), however their contribution to LTP has been a subject of unresolved debate (Bashir et al, 1993;Bortolotto et al, 1995;Chinestra et al, 1993;Manzoni et al, 1994;Richter-Levin et al, 1994;Riedel et al, 1995;Selig et al, 1995). To date, eight mGluR subtypes, designated mGluR1 to mGluR8, have been cloned from the mammalian brain.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the mGluR antagonist, MCPG, can block high frequency stimulation-induced long-term potentiation at the Schaffer collateral-CA1 synapse (7,(26)(27)(28)(29)(30). Several other groups have reported that they cannot block long-term potentiation under apparently identical conditions (31)(32)(33)(34)(35). The lack of truly selective pharmacology of these mGluR compounds could in part help explain problems in using these drugs to study synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%